In vitro Superoxide Production by Peripheral Neutrophils from Patients with Inflammatory Bowel Disease - O. H. Nielsen; D. Berild; I. Ahnfelt-Rønne (Mediators of Inflammation)
Activated polymorphonuclear leucocytes, which are accumulated in inflammatory lesions of inflammatory bowel disease, produce tissue destructive, oxygen derived free radicals and other inflammatory mediators. The PMN superoxide production elicited by formyl-methionyl-leucyl-phenylalanine or the complement split product 5a were compared in IBD and healthy volunteers. Significantly reduced superoxide production was found in PMNs from patients with Crohn's disease as compared to normal controls, when fMLP or CSa were used as stimulants (p<0.001 and p<0.01, respectively), whereas no differences were found when ulcerative colitis patients were compared to normal controls (p>0.05). The enhanced oxygen derived free radical production previously reported in active IBD, and especially in CD intestinal lesions, may either be due to an accumulation of productive phagocytes or to a change of the inflammatory profile of these cells when migrating into intestinal lesions, possibly due to interaction with other mediators (e.g. adhesion molecules and interleukins).